The (mis)use of paratexts to (mis)represent the Other: Chun Sue’s Beijing Doll as a case study - Rovira-Esteva, Sara (Onomázein, 2016)
Translation is believed to be the site par excellence of intercultural encounter and exchange, but how this exchange takes place differs enormously depending on the cultures and literature systems that come into contact. Different cultures have different views on the function of source texts in translation and different expectations about the role of the translator. They therefore have different translation norms that have an impact on the final product, i.e. the translated text. Power relations between cultures are also reflected in a translator’s approach to the translation task, and the way in which publishers present translated texts to their target audiences. Translation has, therefore, a social and ideological dimension. By analyzing three translations (into English, Catalan and Spanish) of Chun Sue’s Beijing Wawa (Beijing Doll), a Chinese chick lit autobiographical narrative, I will show how different strategies used in transferring paratextual elements across linguistic and cultural boundaries in these translations reflect different degrees of intercultural sensitivity and different ways of representing the Other. All three translations from Chinese evidence a tendency to manipulate the appearance of the source text or even to appropriate the Other, resulting in a reshaping of the author’s image of herself. Consequently, the function and status of the text in the literary system of the target culture is modified. Some of the paradoxes evidenced as a result of publishers’ re-presentation of the original for their target audiences are reflected upon, and conclusions drawn.